Pengaruh Kualitas Makanan, Suasana Dan Kewajaran Harga Terhadap Kepuasan Pelanggan (Studi pada Cafe Photokopi di Kota Malang) - Mega Lestari; Abdul Kodir Djaelani; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to influence food quality, atmosphere, and price fairness on customer satisfaction partially or simultaneously. This research method uses quantitative methods and this type of research is explanatory research. The sample of this research was 88 customers at Photocopi Cafe Malang using the Slovin formula with a level of 10%. To obtain accurate and detailed data, this study uses a data collection method with a questionnaire with a Likert scale by distributing it to customers of Cafe Photocopi Malang. Data analysis used was instrument test, normality test, multiple linear regression analysis, classical assumptions, and hypothesis testing using SPSS 20 for Windows. The results of this study indicate that food quality, atmosphere, and price reasonableness simultaneously affect customers at Cafe Photocopi Malang. While partially the quality of food affects customer satisfaction, atmosphere affects customer satisfaction and price fairness affects customer satisfaction at Cafe Photocopi Malang.Keywords: Food Quality, Atmosphere, Fairness of Prices and Customer Satisfaction.